The influence of the force-velocity mechanical properties of upper limb on throwing performance in young experienced handball players - Zhang, Q. S.; Eymard, N.; Hautier, C. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Overarm throwing is considered one of the most critical actions in handball sports related to the gain of competition, which requires the players to throw as fast and accurately as possible to score a goal. It is well known that the overarm throw is a typical ballistics movement that requires the athlete to accelerate a given ball as much as possible to reach the highest throwing velocity in the shortest amount of time (1). Although previous studies have proposed fundamental methods for quantifying upper-limb explosive capacity, such as the ballistics bench press, the Force-Velocity (F-V) mechanical properties obtained during the ballistics bench press have not explored its association with the throwing performance. Thus, the present study aimed to investigate the F-V mechanical properties obtained during the ballistics bench press with a different type of throwing performance in handball players